114k views
12 votes
Y=6x-1, y=3x-4 the solution is_____

1 Answer

13 votes

Answer:

y= -7 and x= -1

Explanation:

To do this, line up the variables so it looks like this...

y-6x=-1

y-3x=-4

The reason why -6x and -3y changes to negative is because that it moved to the other side of the equation.

distribute negative to the bottom equation because the two equations have the same number variable which is y...

y-6x=-1

-y+3x=4

Y cancels out and it will be left with -3x = 3.

X = -1.... plug that in to any of the two equation and you get y = -7.

Hope I helped and have a nice day!!

User Configbug
by
6.3k points